2024
DOI: 10.1111/all.16098
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in pediatric anaphylaxis triggers and management across Asia

Agnes Sze Yin Leung,
Elizabeth Huiwen Tham,
Punchama Pacharn
et al.

Abstract: BackgroundThe epidemiology and management of anaphylaxis are not well‐reported in Asia.MethodsA regional pediatric anaphylaxis registry was established by the Asia‐Pacific Research Network for Anaphylaxis (APRA), using standardized protocols for prospective data collection, to evaluate the triggers and management of anaphylaxis in the Asia‐Pacific region. Pediatric patients below 18 years presenting with anaphylaxis across four Asian countries/cities (Thailand, Singapore, Hong Kong (HK), and Qingdao) were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…We observed unique triggers of anaphylaxis specific to the Asia-Pacific region [3,29]. Shellfish allergy was more common in Asian countries [7,30] and our study found a similar pattern of shellfish anaphylaxis with predominance in adolescence.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We observed unique triggers of anaphylaxis specific to the Asia-Pacific region [3,29]. Shellfish allergy was more common in Asian countries [7,30] and our study found a similar pattern of shellfish anaphylaxis with predominance in adolescence.…”
Section: Discussionsupporting
confidence: 75%
“…Our study reflected the presence of NSAID hypersensitivity in the Asia-Pacific region [33] and served as an unfortunate reminder of its widespread use as 21.2% of NSAID anaphylaxis patients reported prior reactions. While wheat was among the top three triggers of food anaphylaxis in Thailand, Korea and China [27,29,34], it was less common in our population.…”
Section: Patient Characteristics N = 1188 (%)mentioning
confidence: 61%
“…A small number of studies suggest that FA/anaphylaxis presentations may be increasing in Asia in line with other countries. Even within Asia, there is significant heterogeneity in estimated rates of anaphylaxis, with the lowest rates observed in Qingdao in mainland China (1/10 5 population/year), followed by Hong Kong (11/10 5 ), Singapore (21/10 5 ) and Thailand (21-25/10 5 ) [6]. Shellfish was the major trigger in all countries, but curiously peanut allergy was reported as absent in Qingdao and Thailand.…”
mentioning
confidence: 99%
“…While the study by Goh et al was not designed to examine risk factors for this increase, other studies describe the highest rates of FA/anaphylaxis in the most urbanized and population dense centres of Asia. This may reflect a so-called 'westernized lifestyle', associated with dietary habits, composition of gut microbiota, socio-economic status, city versus rural residency but in Asia, not necessarily exposure or timing of introduction of common allergenic foods [5,6]. One needs to acknowledge the many potential caveats associated with use of hospital-derived data in these studies [5,6], such as coding errors, anaphylaxis treatment guidelines and hospital admission policies, difficulty differentiating between unique or multiple presentations by the same individual, changes in patient health-seeking behaviour, availability of community care, more effective anaphylaxis treatment in the community or availability of adrenaline autoinjectors for self-administration.…”
mentioning
confidence: 99%